Application of the Jigsaw Learning Model to Improve Learning Outcomes in History Subjects Class XI-4 at SMA Negeri 14 Medan - Ramadayani, Nova; Sumantri, Pulung; Gultom, Imelga Megawati (CV. Rayyan Dwi Bharata, 2024)
This study seeks to enhance student learning achievements by implementing the Jigsaw learning model with Class XI-4 at SMA NEGERI 14 Medan. Currently, the learning outcomes and student engagement have not met expectations. Learning methods that are inappropriate and do not suit students' characteristics in implementing learning are one of the causes of the learning outcomes and student activity that are not achieved as expected. In using jigsaw learning, students work in small groups to solve tasks that have been divided, each group member is responsible for studying and understanding part of the learning material and then sharing their knowledge with other group members. In this process, In this approach, each student specializes in a specific section of the material and gains a deeper comprehension through teamwork with their peers on the content provided by the teacher. The findings of this study demonstrate that applying the Jigsaw learning model effectively enhances history learning outcomes for Class XI-4 at SMA NEGERI 14 Medan. The research indicates a notable improvement in student performance, with scores rising from 65.5% in the first cycle to 86.9% in the second cycle. Additionally, the study highlights improvements in students' communication, collaboration, and respect for the opinions and contributions of other groups.